Impact of Glycoprotein IIb/IIIa Inhibitors Use on Outcomes After Lower Extremity Endovascular Interventions From Nationwide Inpatient Sample (2006–2011). Issue 4 (23rd February 2016) - Arora, Shilpkumar; Panaich, Sidakpal S.; Patel, Nilay; Patel, Nileshkumar J.; Lahewala, Sopan; Thakkar, Badal; Savani, Chirag; Jhamnani, Sunny; Singh, Vikas; Patel, Nish; Patel, Samir; Sonani, Rajesh; et al.
Abstract : Objective: The aim of our study was to study the impact of glycoprotein IIb/IIIa inhibitors (GPI) on in‐hospital outcomes. Background: There is paucity of data regarding the impact of GPI on the outcomes following peripheral endovascular interventions. Methods: The study cohort was derived from Healthcare Cost and Utilization Project (HCUP) Nationwide Inpatient Sample (NIS) database between the years 2006 and 2011. Peripheral endovascular interventions and GPI utilization were identified using appropriate ICD‐9 Diagnostic and procedural codes. Two‐level hierarchical multivariate mixed models were created. The study outcomes were: primary (in‐hospital mortality and amputation studied separately) and secondary (composite of in‐hospital mortality and postprocedural complications). Hospitalization costs were also assessed. Results: GPI utilization (OR, 95% CI, P ‐value) was independently predictive of lower amputation rates (0.36, 0.27–0.49, <0.001). There was no significant difference in terms of in‐hospital mortality (0.59, 0.31–1.14, P 0.117), although GPI use predicted worse secondary outcomes (1.23, 1.03–1.47, 0.023). Following propensity matching, the amputation rate was lower (3.2% vs. 8%, P < 0.001), while hospitalization costs were higher in the cohort that received GPI (21, 091 ± 404 vs. 19, 407 ± 133, P < 0.001). Conclusions: Multivariate analysis revealed GPI use in peripheral endovascular interventions to be suggestive of an increase in composite end‐point of in‐hospital mortality and postprocedural complications, no impact on in‐hospital mortality alone, significantly lower rate of amputation, and increase in hospitalization costs. © 2016 Wiley Periodicals, Inc.